Análisis de la recaudación del impuesto a la renta sobre personas naturales y jurídicas en el cantón Machala, provincia de El Oro, periodo 2022-2023 - Carrión Chamba, Lenin Tito (2025)
This Curricular Integration Work was developed with the purpose of identifying and comparing the income tax collection of individuals and legal entities in the canton of Machala in the 2022-2023 period, given the absence of previous studies that quantify and analyze the behavior of the collection of this tax in the canton. In addition, the research highlights aspects of the canton's economy that make Machala one of the 10 most important cities in Ecuador and determines the canton's contribution to national income tax collection. The research is descriptive, with a quantitative approach and a non-experimental longitudinal design, and integrates macroeconomic indicators, bulletins, sectoral files and reports that support the variations in the canton's income tax collection during the period under analysis. The results revealed that the collection of income tax from individuals and corporations decreased in 2023, thus reducing by 12.75% the overall income tax collection of this canton. However, the subtypes of income tax that increased their collection in that period were income tax on inheritances, legacies and donations, the single income tax on the profit on the sale of shares from companies domiciled in Ecuadorian territory and voluntary advances. Finally, the main causes associated with the collection decline are described, the percentage variation of the amounts collected in each subtype of income tax, the percentage structure of the overall income tax, and the contribution of the city of Machala to income tax collection at the different levels of territorial organization are presented.